2014
DOI: 10.1186/s13000-014-0176-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Gene expression profiles analysis identifies key genes for acute lung injury in patients with sepsis

Abstract: BackgroundTo identify critical genes and biological pathways in acute lung injury (ALI), a comparative analysis of gene expression profiles of patients with ALI + sepsis compared with patients with sepsis alone were performed with bioinformatic tools.MethodsGSE10474 was downloaded from Gene Expression Omnibus, including a collective of 13 whole blood samples with ALI + sepsis and 21 whole blood samples with sepsis alone. After pre-treatment with robust multichip averaging (RMA) method, differential analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…L-palmitoylcarnitine facilitates the transport of long-chain fatty acids from the cytoplasm into the mitochondria, where fatty acid beta-oxidation takes place. During acute lung injury, fatty acid metabolism is disturbed (Guo, et al, 2014). A previous study also showed that high levels of L-palmitoylcarnitine were associated with poorer prognosis in patients with chronic heart failure (Ueland, et al, 2013).…”
Section: Tablementioning
confidence: 99%
“…L-palmitoylcarnitine facilitates the transport of long-chain fatty acids from the cytoplasm into the mitochondria, where fatty acid beta-oxidation takes place. During acute lung injury, fatty acid metabolism is disturbed (Guo, et al, 2014). A previous study also showed that high levels of L-palmitoylcarnitine were associated with poorer prognosis in patients with chronic heart failure (Ueland, et al, 2013).…”
Section: Tablementioning
confidence: 99%
“…41 Furthermore, Guo et al identified that GO functions associated with PCNA were involved in negative regulation of cell proliferation. 42 Therefore, downregulated expression of PCNA gene in sepsis suggested PCNA might be an important gene involving in sepsis. SMAD4 gene encodes a protein of SMAD family member 4 which is activated by transmembrane serine-threonine receptor kinases as TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chen et al (7) have used the same expression profile (6) to further discover 12 differentially expressed genes (DEGs) and 7 important functions. Guo et al (8) also used this microarray data to identify several key genes (PTK2, SRC and CAV2) for ALI in patients with sepsis. Although these studies are helpful to reveal the molecular mechanism of ALI, the DEGs obtained in these studies were not consistent.…”
Section: Introductionmentioning
confidence: 99%